PLZF is a negative regulator of retinoic acid receptor transcriptional activity - Martin, Perrine J (BioMed Central, 2003)
BACKGROUND: Retinoic acid receptors (RARs) are ligand-regulated transcription factors controlling cellular proliferation and differentiation. Receptor-interacting proteins such as corepressors and coactivators play a crucial role in specifying the overall transcriptional activity of the receptor in response to ligand treatment. Little is known however on how receptor activity is controlled by intermediary factors which interact with RARs in a ligand-independent manner. RESULTS: We have identified the promyelocytic leukemia zinc finger protein (PLZF), a transcriptional corepressor, to be a RAR-interacting protein using the yeast two-hybrid assay. We confirmed this interaction by GST-pull down assays and show that the PLZF N-terminal zinc finger domain is necessary and sufficient for PLZF to bind RAR. The RAR ligand binding domain displayed the highest affinity for PLZF, but corepressor and coactivator binding interfaces did not contribute to PLZF recruitment. The interaction was ligand-independent and correlated to a decreased transcriptional activity of the RXR-RAR heterodimer upon overexpression of PLZF. A similar transcriptional interference could be observed with the estrogen receptor alpha and the glucocorticoid receptor. We further show that PLZF is likely to act by preventing RXR-RAR heterodimerization, both in-vitro and in intact cells. CONCLUSION: Thus RAR and PLZF interact physically and functionally. Intriguingly, these two transcription factors play a determining role in hematopoiesis and regionalization of the hindbrain and may, upon chromosomal translocation, form fusion proteins. Our observations therefore define a novel mechanism by which RARs activity may be controlled.